1999
DOI: 10.1016/s0002-9440(10)65319-9
|View full text |Cite
|
Sign up to set email alerts
|

Trisomies 8 and 20 Characterize a Subgroup of Benign Fibrous Lesions Arising in Both Soft Tissue and Bone

Abstract: Desmoid tumor, desmoplastic fibroma, periosteal desmoid tumor, osteofibrous dysplasia and fibrous dysplasia are benign mesenchymal lesions arising in soft tissue or bone. Desmoid tumors, also known as aggressive fibromatosis or fibromatosis of soft tissue, may occur in extraabdominal, abdominal, or intra-abdominal locations. Desmoplastic fibroma and periosteal desmoid tumor, identical histologically, differ only by location. Desmoplastic fibroma and periosteal desmoid tumor are considered to represent the bone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
40
0
1

Year Published

2001
2001
2014
2014

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 96 publications
(41 citation statements)
references
References 22 publications
0
40
0
1
Order By: Relevance
“…Mutations in both b-catenin and APC (adenomatous polyposis coli) genes have been implicated in the pathogenesis of desmoid-type fibromatosis [6]. Fluoroscent in situ hybridization (FISH) analyses have demonstrated trisomy 8 and 20 as nonrandom aberrations in benign fibrous conditions of both bone and soft tissue [7]. Moreover, DFs of gnathic bones have been diagnosed in patients with the hamartoneoplastic syndrome-tuberous sclerosis, in which they are believed to represent intraoral manifestations of this multisystem genetic disorder [8,9].…”
Section: Discussionmentioning
confidence: 99%
“…Mutations in both b-catenin and APC (adenomatous polyposis coli) genes have been implicated in the pathogenesis of desmoid-type fibromatosis [6]. Fluoroscent in situ hybridization (FISH) analyses have demonstrated trisomy 8 and 20 as nonrandom aberrations in benign fibrous conditions of both bone and soft tissue [7]. Moreover, DFs of gnathic bones have been diagnosed in patients with the hamartoneoplastic syndrome-tuberous sclerosis, in which they are believed to represent intraoral manifestations of this multisystem genetic disorder [8,9].…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, because of their rarity, cytogenetic reports concerning these tumors are few. [2][3][4][5][6][7] The karyotypic findings of only five cases of classic adamantinoma and two cases of differentiated adamantinoma have been described, [2][3][4] Table 1. An examination of the four current cases and a review of those previously reported reveal that extra copies of chromosomes 7,8,12,19, and/or 21 have been seen in all but one case of classic adamantinoma and one case of differentiated adamantinoma.…”
Section: Discussionmentioning
confidence: 99%
“…The following primary abnormal clone and subclone were detected in Case 2: 54,XY,ϩ5,ϩ7,ϩ8,ϩ12,ϩ12,ϩ14, ϩ19, ϩ21 [6]/53, XY, ϩ4, ϩ5, ϩ7, ϩ8, ϩ12, ϩ14, Ϫ16, ϩ17, Ϫ18,ϩ21,ϩmar [2]. A representative karyotype of the primary clone is presented in Figure 4.…”
Section: Cytogeneticsmentioning
confidence: 98%
See 2 more Smart Citations